2019
DOI: 10.1016/j.seizure.2019.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of closed-loop vagal nerve stimulation in patients with refractory epilepsy

Abstract: The AspireSR® is a vagal nerve stimulation (VNS) device that operates as a closed-loop system, delivering an automatic stimulation in response to an ictal heart rate increase that serves as a predictor for an imminent seizure.Our purpose is to assess the outcome of the AspireSR® in a patient population managed in a pediatric neurology unit. Methods: The records of patients who underwent transplantation during 2015-2017 and are continuously followed in one pediatric-epilepsy clinic, were retrospectively analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…After 18 months of rVNS therapy, 69.2% (n = 9) of study participants had ≥50% reduction in seizure frequency, although no statistically significant changes in seizure frequency were detected. Tzadok et al reported ≥50% reduction in seizure frequency in 62% of VNS-naïve patients at a mean follow-up of 13 months [15], results similar to those obtained in this study.…”
Section: The Efficacy Of Rvns Therapysupporting
confidence: 91%
See 1 more Smart Citation
“…After 18 months of rVNS therapy, 69.2% (n = 9) of study participants had ≥50% reduction in seizure frequency, although no statistically significant changes in seizure frequency were detected. Tzadok et al reported ≥50% reduction in seizure frequency in 62% of VNS-naïve patients at a mean follow-up of 13 months [15], results similar to those obtained in this study.…”
Section: The Efficacy Of Rvns Therapysupporting
confidence: 91%
“…Literature has established an association between sudden increases in heart rate and seizure onset, making tachycardia a surrogate marker for seizure activity [1,10]. Newer responsive VNS (rVNS) generators, such as the AspireSR (Cyberonics, Houston, Texas, USA), take advantage of this seizure marker to abort breakthrough seizures [11][12][13][14][15]. Specifically, the rVNS incorporates a closed-loop feature, known as Automatic Stimulation Mode (AutoStim), to send electrical impulses to the left vagus nerve upon the detection of ictal tachycardia, allowing vagal stimulation shortly after seizure onset.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works dealing with the closed-loop vagus nerve stimulation have already shown that it is possible to adaptively control the heart rate in sheep or pigs [ 27 , 28 ], as well as to reduce seizure frequency in epileptic patients with heart rate triggered stimulation bursts [ 29 ]. However, these studies all used invasive cervical vagus nerve stimulators.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, none of these studies were designed or powered to evaluate long‐term outcome. Two additional uncontrolled studies (7,8) suggested that cardiac‐based closed‐loop VNS offered better results than conventional VNS in heterogeneous patient populations.…”
Section: Introductionmentioning
confidence: 99%